Alcohol‑induced attenuation of post‑traumatic inflammation is not necessarily liver‑protective following trauma/hemorrhage. - Wagner, Nils; Dieteren, Scott; Franz, Niklas; Koehler, Kernt; Perl, Mario; Marzi, Ingo; Relja, Borna (International Journal of Molecular Medicine, 2019)
Due to their high prevalence, blunt chest trauma (TxT) and hemorrhagic shock have a significant influence on the outcomes of trauma patients, causing severe modulations of the immune system and high mortality rates. Alcohol consumption in trauma patients has a high clinical impact. Studies investigating the timing of alcohol intoxication prior to trauma are limited, although there are two typical scenarios regarding alcohol consumption: Acute ('drink and drive scenario') and sub‑acute ('evening binge drinking'). Therefore, the present study investigated the influence of either an acute or sub‑acute alcohol‑drinking scenario in an in vivo model of TxT and hemorrhagic shock, focusing on liver inflammation and outcomes. At 12 h (sub‑acute) or 2 h (acute) before the experiment, female Lewis rats received a single oral dose of alcohol (ethanol, EtOH) or saline (NaCl, ctrl), followed by TxT, hemorrhagic shock (35±3 mm Hg) and resuscitation (H/R). The animals were either sacrificed 2 h later or their survival was determined for 72 h. The results revealed that EtOH induced significant fatty changes in the liver. TxT + H/R‑induced increases in the gene expression of interleukin (IL)‑6 and intercellular adhesion molecule‑1 and the protein expression of tumor necrosis factor (TNF)‑α and IL‑1β were significantly reduced in both EtOH groups compared with those in the corresponding TxT + H/R ctrl groups. The local presence of IL‑10‑expressing cells in the liver was significantly increased following TxT + H/R in all groups, although the sub‑acute EtOH TxT + H/R group had a significantly higher proportion of IL‑10‑positive cells compared with all other groups. Stimulating peripheral whole blood with lipopolysaccharide led to significantly lower levels of TNF‑α release in the sub‑acute EtOH group compared with the levels in all other groups. Significant TxT + H/R‑induced increases in liver transaminases and liver damage were most prominent in the sub‑acute EtOH group. The TxT + H/R EtOH group exhibited the lowest levels of glucose. There were no significant differences in mortality rate among the TxT + H/R groups. The data obtained indicates that the severity of liver damage following TxT + H/R may depend on the timing of alcohol consumption and severity of trauma, but also on the balance between pro‑ and anti‑inflammatory responses.
EVALuna2:415869